2022
DOI: 10.1186/s13059-022-02763-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental genomes segregate into distinct blastomeres during multipolar zygotic divisions leading to mixoploid and chimeric blastocysts

Abstract: Background During normal zygotic division, two haploid parental genomes replicate, unite and segregate into two biparental diploid blastomeres. Results Contrary to this fundamental biological tenet, we demonstrate here that parental genomes can segregate to distinct blastomeres during the zygotic division resulting in haploid or uniparental diploid and polyploid cells, a phenomenon coined heterogoneic division. By mapping the genomic landscape of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 144 publications
5
15
0
Order By: Relevance
“…With regard to abnormal cleavage events, we found lower developmental capacity in zygotes with multipolar cleavage or ruffling membrane, which is in line with human studies 29,37 and recent publications in human and bovine zygotes that showed how multipolar division leads to lower embryo development compared to normal cleavers 30,34 . As supported by the higher number of nuclear abnormalities following multipolar zygotic division, multipolar zygotic division seems to be associated with genome segregation errors in embryos leading to a higher frequency of mixoploidy, and chromosomal abnormalities in the resultant embryos 33,39,41 and embryonic arrest 30 . 31,36,38 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With regard to abnormal cleavage events, we found lower developmental capacity in zygotes with multipolar cleavage or ruffling membrane, which is in line with human studies 29,37 and recent publications in human and bovine zygotes that showed how multipolar division leads to lower embryo development compared to normal cleavers 30,34 . As supported by the higher number of nuclear abnormalities following multipolar zygotic division, multipolar zygotic division seems to be associated with genome segregation errors in embryos leading to a higher frequency of mixoploidy, and chromosomal abnormalities in the resultant embryos 33,39,41 and embryonic arrest 30 . 31,36,38 .…”
Section: Discussionsupporting
confidence: 91%
“…Time-lapse technology enables non-invasive and continuous observation of embryo development from fertilization to transfer. This technology has been used in human studies to detect key events that predict blastocyst formation, ploidy, and embryo implantation potential and it is applied in some fertility clinics for its technical benefits and to select the best embryos for transfer (reviewed by Pennetta et al) 27,28. Morphokinetic parameters have been linked to embryo development and chromosomal or genome-wide errors 29,30 . For example, the pace of development of in vitro produced embryos can be linked to embryo quality, and embryos that cleave faster following fertilization are more developmentally competent than are those that cleave relatively late 31,32 .…”
Section: Embryo Morphokinetics Derived From Fresh and Vitrified Bovin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dual spindles were also observed in bovine embryos 34 . A study of bovine embryos showed that parental genomes segregated to distinct blastomeres during the rst division, resulting in haploid or uniparental diploid and polyploid cells 39 . This phenomenon is presumed to occur because parental chromosomes are segregated into two groups and can form heterogeneous cells 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike mitotic errors at the zygote stage ( Figure 1C ), a mitotic mis-segregation event that arises in 2-cell embryos or later in development can produce cells with diverse karyotypes known as chromosomal mosaicism ( Figure 1D ). Euploid-aneuploid mosaic embryos containing a mixture of both chromosomally normal and abnormal cells are the most common ( Chuang et al, 2020 ), but there are also reports of embryos with mixoploidy, whereby cells differ according to whether they are haploid, diploid, or polyploid ( Destouni et al, 2016 ; Carson et al, 2018 ; Daughtry et al, 2019 ; De Coster et al, 2022 ). However, these types of errors typically go undetected and/or are classified as euploid unless parental DNA is inputted to assign chromosomes as either maternal or paternal.…”
Section: Mitotic Mis-segregation Events Often Lead To Chromosomal Mos...mentioning
confidence: 99%